Calibração do modelo de superfície Noah LSM: aplicação em uma região agrícola no Sul do Brasil - Gonçalves, Juliana Bittencourt (2016)
In this study, simulated to net radiation and energy flux in a region with rotation of crops, for two distinct periods: Period 1 (01 / Feb / 2009 to 31 / Jan / 2010) and period 2 (14 / Dec / 2009 to 28 / Apr / 2010). In these simulations we used the NOAH LSM surface model. For the period 1 initially, without any calibration simulations were performed only with the input of the local weather conditions, an adjustment of an experiment controlfile file and spin up for the stabilization of the initial conditions. In these simulations, the results were very poor, indicating a need to test the sensitivity of the model especially because of the launch conditions of temperature and soil moisture. After these tests it was found that the initial predictions of impact can be considerable conditions for the two cases. It is noticed that the soil moisture changes generate greater impact in the model that temperature variations boot. As a result, proposed a calibration for the model. The calibration method was to make some simulations manually varying the parameters of soil and vegetation, or both, according to the deficiencies of the NOAH LSM. The tests were carried out until they could get a more optimized forecast for the period studied. The initial analysis of the local conditions of the experimental site was very important for calibration, as it allowed establishing previous parameters corresponding to values close to those parameters when calibrated. Simulation results after calibration applied satisfactorily exhibited liquid radiation and heat flows. So it can be said that the calibration is proposed representing characteristics of vegetation and soil correctly. Nevertheless, the corrections that the model still needs, especially in sensible and latent heat fluxes, may be associated with representation in heat distribution processes and water, or by the fact that the colder months had considerable regime rains. So when there is cloud cover, the model still has problems in representation. Results for long periods of data, as in this work, may lose some of representativeness due to the seasonality of the vegetation parameters, for which varied the parameters for periods culture and fallow. The most important contribution made in this work was a model fit for an agricultural ecosystem area and validate it for the future, it may be used as an initial boundary condition in numerical weather prediction models. The implementation variations in LAI and albedo parameter applied in the simulations of period 2 (soybean) improved the description of the heat flux and net radiation.